Mechanical Activation by Ball Milling as a Strategy to Prepare Highly Soluble Pharmaceutical Formulations in the Form of Co-Amorphous, Co-Crystals, or Polymorphs - Luz María Martínez; Jorge Cruz-Angeles; Mónica Vázquez-Dávila; Eduardo Martínez; Paulina Cabada; Columba Navarrete-Bernal; Flor Cortez (MDPI AG, 2022)
Almost half of orally administered active pharmaceutical ingredients (APIs) have low solubility, which affects their bioavailability. In the last two decades, several alternatives have been proposed to modify the crystalline structure of APIs to improve their solubility; these strategies consist of inducing supramolecular structural changes in the active pharmaceutical ingredients, such as the amorphization and preparation of co-crystals or polymorphs. Since many APIs are thermosensitive, non-thermal emerging alternative techniques, such as mechanical activation by milling, have become increasingly common as a preparation method for drug formulations. This review summarizes the recent research in preparing pharmaceutical formulations (co-amorphous, co-crystals, and polymorphs) through ball milling to enhance the physicochemical properties of active pharmaceutical ingredients. This report includes detailed experimental milling conditions (instrumentation, temperature, time, solvent, etc.), as well as solubility, bioavailability, structural, and thermal stability data. The results and description of characterization techniques to determine the structural modifications resulting from transforming a pure crystalline API into a co-crystal, polymorph, or co-amorphous system are presented. Additionally, the characterization methodologies and results of intermolecular interactions induced by mechanical activation are discussed to explain the properties of the pharmaceutical formulations obtained after the ball milling process.